Integration of geospatial databases in rural land regularization: Reduction of cadastral inconsistencies (Research, Society and Development, 2026)
Rural land regularization in Brazil relies on consistent, interoperable spatial information. However, the coexistence of geospatial databases with different purposes, scales, and validation levels has fostered overlaps, perimeter discrepancies, and cadastral ambiguities, with direct impacts on the efficiency of georeferencing workflows and legal certainty. This study aimed to analyze, in the Brazilian context, recent evidence on geospatial database integration applied to rural land regularization, emphasizing contributions of geoprocessing to reduce cadastral inconsistencies and operational rework. Methodologically, a systematic literature review (2021 to 2026) was conducted, with searches in widely covered scientific databases and portals. Portuguese and English descriptors were used for georeferencing, land regularization, the Rural Environmental Registry (CAR), SIGEF, interoperability, validation, and overlap, followed by eligibility screening and a thematic narrative synthesis. The results and discussion indicate that informational fragmentation between self declared registries and certified databases is a structural driver of geometric and semantic inconsistencies, increasing the analysis backlog and inducing successive corrections across certification, validation, and registration stages. The reviewed literature further indicates that integration strategies supported by data governance, unique property identification, reliability hierarchies, and automated routines for topological control and cross validation tend to anticipate discrepancies, improve inter database consistency, and reduce rework in georeferencing. The findings support the hypothesis that integrating geospatial databases, when technically structured and institutionally coordinated, helps mitigate cadastral inconsistencies and optimize rural land regularization processes, strengthening legal certainty and territorial governance.